Linking Bank Crises and Sovereign Defaults: Evidence from Emerging Markets. Issue Volume 66:Issues 4(2018) (December 2018) - Balteanu, Irina; Erce, Aitor
Abstract We analyze the mechanisms through which bank and sovereign distress feed into each other, using a large sample of emerging market economies over three decades. After defining "twin crises" as events where bank crises and sovereign defaults combine, and further distinguishing between those bank crises that end up in sovereign defaults and vice versa, we study what differentiates "single" and "twin" events. Using an event analysis methodology, we document systematic differences between "single" and "twin" crises across various dimensions including the balance sheet interconnection between banks and the sovereign, banking sector characteristics, the state of public finances, the macroeconomic environment and financial openness. The importance of these characteristics in shaping the transmission of stress between banks and sovereigns is confirmed by two alternative discrete-variable multivariate approaches. We also show that "twin" crises themselves are heterogeneous events: taking into account the actual time sequence of crises that compose "twin" episodes is important for understanding their channels of transmission and economic consequences. These findings inform the flourishing theoretical literature on the mechanisms surrounding feedback loops of sovereign and bank stress.